STRATEGI KOMUNIKASI PEMBANGUNAN PERTANIAN: ANALISA BIBLIOMETRIK LIMA DEKADE (1974-2024) - Riski, Abdul; As'adi, Mohamad Hasan (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
This study conducts a comprehensive bibliometric analysis to map the evolution and research trends in agricultural development communication strategies over five decades (1974–2024). A dataset of 592 documents retrieved from Scopus was analyzed using biblioshiny. The results demonstrate a marked exponential growth in publications, particularly from 2021 onward, underscoring the rising global scholarly interest in this domain. Sustainability (Switzerland) was identified as the most prolific journal, while Wageningen University & Research emerged as the most active contributing institution. The most cited publication, Hard choices: Making trade-offs between biodiversity conservation and human well-being, amassed 705 citations, highlighting the critical discourse between conservation priorities and human welfare. Thematic evolution analysis reveals a distinct shift from early research foci on strategic planning and rural policy toward contemporary themes, including sustainable development, decision-making processes, and the adoption of digital technologies such as the Internet of Things. Network analysis indicates that the United States serves as the central hub for international collaboration, although significant research gaps persist across numerous regions. As the first holistic and longitudinal bibliometric study in this field, this research provides an unprecedented and structured literature map. It offers valuable guidance for scholars in defining future research agendas, selecting appropriate publication venues, and fostering academic collaborations, particularly within the interrelated areas of communication strategy, agricultural sustainability, and digital transformation.